Prophylactic injection of non-citrullinated α-enolase has immunomodulatory effects in collagen-induced arthritis mice. (22nd February 2012) - Guillou, C; Avenel, G; Derambure, C; Le Loarer, F; Verdet, M; Hiron, M; Maho, M; Le-Loet, X; Adriouch, S; Sabourin, J C; Boyer, O; Lequerre, T; et al.
Abstract : Background: Identification of autoantibodies associated with rheumatoid arthritis (RA) has been of major interest. In this context, the authors have previously identified for the first time α-enolase as a new auto-antigen in early RA. Moreover, subsequent studies have shown that citrullination of α-enolase is crucial for its autoantigenicity. α-enolase is an evolutionary conserved protein implicated both in glycolysis pathway and as a plasminogen receptor. Here, the authors have evaluated, in the well-known collagen induced arthritis model, the clinical, immunological and histological effects of both recombinant non-citrullinated α-enolase and immunodominant peptides from human and bacterial species. Methods: Different doses of α-enolase (10 and 100 µg) or immunodominant enolase peptide 1 from human (hEP1) or porphyromonas Gingivalis (pEP1) (10 or 100µg) were intraperitoneally injected to 6 week-old DBA/1 mice one day prior to collagen II arthritis induction (CIA). Both clinical (weight, arthritis score, tarsal thickness) and biological (anticollagen II and anti-α-enolase antibodies) were assessed during the 90 days follow-up period. Four histological score were also assessed: inflammation, syniovial thickening, cartilage resorption and bone resorption. Results: Prophylactic injection of recombinant α-enolase was able to significantly prevent weight loss and to decrease the severity of arthritis evaluated by the arthritis score as well as the tarsal thickness. There was a dose-effect since 100 µg led to better results. Levels of anticollagen II antibodies were significantly lower whereas titers of anti-α-enolase antibodies were significantly higher in mice treated with 100 µg of α-enolase compared to control mice. Moreover, histological score were in agreement with clinical score. As regards to hEP1 and pEP1, the authors etablished a dose-dependant protective effect in CIA which is significant for pEP1. This protective effect is not due to once again a decrease of anti-collagen II antibodies titer. Conclusion: Prophylactic treatment with recombinant α-enolase suggest a protective role of this molecule. The clinical effect is not due to an imunological response mediated by anti-α-enolase antibodies. Prophylactic injection could induce either an immune deviation or an emergence of regulatory lymphocyte population, responsible of a decrease of anti-CII antibodies production. These results suggest α-enolase has an immunomodulatory effect in CIA mice. Those results suggest that non-citrullinated α-enolase could constitute a potential new therapeutic approach in RA.